Environmental high temperature induced cartilage damage through triggering programmed necrosis mediated by producing left-handed DNA - Sun Yingfei; Yang Feng; Ma Haoning (Ecotoxicology and Environmental Safety)
Amid global climate warming, rising temperatures are becoming a major challenge for public health worldwide. At present, many places in the world frequently encounter extreme high temperature weather, which directly leads to frequent occurrence of heat stroke (HS). Heat stroke may lead to significant organ damage and potentially result in death. However, the impact of heat stroke (HS) on cartilage and osteoarthritis has not been fully revealed, which is an urgent scientific issue to be explored. In the current study, we first established an in vitro chondrocyte model and then explored the toxicological effects of HS on chondrocytes. Experimental data indicate that HS significantly reduces the proliferative activity of chondrocytes. HS triggers oxidative stress and inflammation in chondrocytes. Further biochemical experiments showed that HS caused chondrocytes senescence by detecting a series of senescence marker molecules, such as p21, p16, and p53. We further studied the molecular mechanism of HS-induced cell damage. We found that HS induced genomic damage, generating substantial Z-DNA (left-handed DNA) and activating ZBP-1-mediated programmed cell necrosis, which subsequently released various inflammatory factors. In contrast, inhibition of Z-DNA-mediated activation of ZBP-1 can significantly alleviate aging damage. In in-vivo experiments using a gene-knockout mouse model, our team found that HS induced cartilage aging. Additionally, HS aggravated osteoarthritis in vivo. On this basis, we observed that the expression of FGF1 was reduced under HS conditions. Therefore, we explored the effect of FGF1 on the damage of chondrocytes caused by HS. The experimental data showed that FGF1 activates the AMPK signaling pathway, which effectively alleviating the aging caused by HS. This work lays a solid foundation for further exploration into cartilage damage induced by HS. Our study also simultaneously indicates that FGF1 may be a very promising agent for the treatment of HS causing cartilage damage.